2009
DOI: 10.1007/s00210-009-0409-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E and sodium selenate on impaired contractile activity by bacterial lipopolysaccharide in the rat vas deferens

Abstract: We investigated whether bacterial lipopolysaccharide (LPS) treatment causes any hyporeactivity in rat vas deferens tissue and also whether vitamin E or sodium selenate has any restorative effect on this possible hyporesponsiveness. LPS treatment attenuated contractions to electrical field stimulation (EFS), phenylephrine, or ATP at the prostatic and epididymal ends. Treatment with the inducible nitric oxide synthase (iNOS) inhibitor aminoguanidine or vitamin E could prevent the impairment in contractile respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some recent papers showed that prostatitis elicited by E. coli caused an uncontrolled growth in the prostate gland at the early stages of inflammation (8,9). On the other hand, in previous studies, it was shown that uropathogenic E. coli or bacterial lipopolysaccharide (LPS) treatment causes hypocontractility in various tissues, including vessels, the urinary bladder, the corpus cavernosum, and the vas deferens (10)(11)(12)(13)(14). It might thus be expected that inflammation causes hypocontractility in prostate tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent papers showed that prostatitis elicited by E. coli caused an uncontrolled growth in the prostate gland at the early stages of inflammation (8,9). On the other hand, in previous studies, it was shown that uropathogenic E. coli or bacterial lipopolysaccharide (LPS) treatment causes hypocontractility in various tissues, including vessels, the urinary bladder, the corpus cavernosum, and the vas deferens (10)(11)(12)(13)(14). It might thus be expected that inflammation causes hypocontractility in prostate tissue.…”
Section: Introductionmentioning
confidence: 99%